A Study on Stability Analysis of Non-linear System of a Real-time Dynamic Sub Structuring Model via Neutral Delay Differential Equation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, necessary condition for existence of characteristic roots of Neutral Delay Differential equation to study the stability of a nonlinear system of a mass-spring-damper connected to a pendulum is derived from an real-time dynamic sub structuring model and illustrated with examples.